SEROPREVALENCE AND CLINICAL FEATURES OF SCRUB TYPHUS AMONG FEBRILE PATIENTS IN A TERTIARY CARE HOSPITAL - PANDYA, AHUTI; MEENA, PREETI; JAREDA, KULDEEP (International Journal of Current Pharmaceutical Research, 2024)
Objective: Rickettsial infections is the most neglected and underdiagnosed tropical diseases in developing countries. The most common rickettsial disease, which is caused by the obligate intracellular gram-negative bacteria Orientia tsutsugamushi, is Scrub Typhus. Scrub typhus can prove to an important diagnosis in pyrexia of unknown origin (PUO) patients and is transmitted by a species of trombiculid mites (“chiggers”). Aim of this study is to find seroprevalence and clinical features of scrub typhus among febrile patients from a tertiary care hospital in North India. Methods: This study was undertaken for a period of 1 y. All the patients attending the outpatient department or admitted indoors suspected of PUO were included in the study. Serum samples of suspected cases were tested for IgM Scrub typhus. Results: During the study period, a total of 755 cases were tested for scrub typhus, out of which 223 were positive so, the seroprevlance of Scrub typhus is 29.5%. Out of 223 positive patients, 105 (47%) were males and 118 (53%) were females. Maximum no. of patients was from age group 21 to 40 y of age and maximum number of cases is in autumn season. Most common clinical feature is fever, followed by myalgia, headache, ocular pain, dyspnoea, cough and eschar, respectively. Conclusion: Scrub typhus is an emerging tropical rickettsial disease in the Indian subcontinent. The present study highlights the importance of screening of PUO cases for Scrub typhus as timely institution of simple empirical treatment can prove to be lifesaving in such cases.